2010
DOI: 10.1002/anie.201003168
|View full text |Cite
|
Sign up to set email alerts
|

Selective Modulation of DNA Polymerase Activity by Fixed‐Conformation Nucleoside Analogues

Abstract: Picking a pucker! Fixed‐conformation North (N)‐ and South (S)‐methanocarba‐2′‐deoxyadenosine‐triphosphate (MC‐dATP) have different effects in DNA strand extension catalyzed by HIV‐1 RT and three human Y‐family DNA polymerases (pols). All of the polymerases tested preferred the N‐oriented furanose geometry, though pol η could insert both pucker mimics. The growth of malignant breast cancer cells overexpressing pol ι was more severely inhibited by N‐MC‐dATP than that of nonmalignant breast cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 46 publications
1
21
0
Order By: Relevance
“…Under these conditions, Dpo4 catalysis was slowed nearly 9-fold by S-MC-dATP when compared to the RNA-like pucker of N-MC-dATP. These results are similar to those obtained previously with HIV-1 Reverse Transcriptase (HIV-1 RT) (21) and for human DNA polymerase kappa (hpol κ) (22). In contrast to Dpo4, the B-family member, Dpo1, can catalyze insertion of both N-MC-dATP and S-MC-dATP opposite template dT with relatively modest levels of inhibition by either nucleotide analogue (Figure 1D).…”
Section: Discussionsupporting
confidence: 90%
“…Under these conditions, Dpo4 catalysis was slowed nearly 9-fold by S-MC-dATP when compared to the RNA-like pucker of N-MC-dATP. These results are similar to those obtained previously with HIV-1 Reverse Transcriptase (HIV-1 RT) (21) and for human DNA polymerase kappa (hpol κ) (22). In contrast to Dpo4, the B-family member, Dpo1, can catalyze insertion of both N-MC-dATP and S-MC-dATP opposite template dT with relatively modest levels of inhibition by either nucleotide analogue (Figure 1D).…”
Section: Discussionsupporting
confidence: 90%
“…Yet, it is this feature that appears to explain the increased catalytic efficiency of hpol ι. The stabilized anti conformation results in faster insertion than unmodified dATP, as evidenced by an increased turnover number for N-MC-dATP 37 and also improves the accuracy of hpol ι DNA synthesis opposite dT by increasing the propensity of the enzyme to pair adenine with thymidine. Interestingly, the crystal structure of hpol ι inserting dGTP opposite dT reveals that the incoming dGTP resides in a “Western” type O4′-exo pucker ( P = 271.2 °).…”
Section: Resultsmentioning
confidence: 99%
“…41 Previous work has examined the conformational preferences of the furanose ring system for different enzyme classes, including three human Y-family DNA polymerases. 37,48 A general conclusion was that polymerases tend to favor C3′-endo, North puckers over C2′-end, South puckers for the incoming dNTP. However, insertion of MC-dNTPs tends to diminish catalytic efficiencies for most polymerases tested.…”
Section: Discussionmentioning
confidence: 99%
“…However, the final biological activity of the nucleosides prodrugs depends on their transport across cell membranes, activation to 5 -mono-, di-, or triphosphate anabolites by viral and/or cellular kinases and their ability to serve as substrates for specific DNA polymerase. It has been reported that different DNA polymerases, including those within a subfamily, show important differences in preferences for the furanose conformation of the sugar moiety during catalysis [12]. The preference of human nucleoside transporters with respect to the sugar ring has been examined using methanocarba-Ado or methanocarba-Cyd in North (N-MCdA and N-MCdC) or South (S-MCdA and S-MCdC) analogs [13].…”
Section: Introductionmentioning
confidence: 99%